Peritraumatic 17β-estradiol levels influence chronic posttraumatic pain outcomes. Issue 12 (December 2021) - Linnstaedt, Sarah D.; Mauck, Matthew C.; Son, Esther Y.; Tungate, Andrew S.; Pan, Yue; Rueckeis, Cathleen; Yu, Shan; Lechner, Megan; Datner, Elizabeth; Cairns, Bruce A.; Danza, Teresa; Velilla, Marc-Anthony; et al.
Abstract : Abstract: Biologic factors that predict risk for and mediate the development of common outcomes of trauma exposure such as chronic posttraumatic pain (CPTP) are poorly understood. In the current study, we examined whether peritraumatic circulating 17β-estradiol (E2) levels influence CPTP trajectories. 17β-estradiol levels were measured in plasma samples (n = 254) collected in the immediate aftermath of trauma exposure from 3 multiethnic longitudinal cohorts of men and women trauma survivors. Chronic posttraumatic pain severity was evaluated 6 weeks, 6 months, and 1 year after traumatic stress exposure. Repeated measures mixed models were used to test the relationship between peritraumatic E2 levels and prospective CPTP. Secondary analyses in a nested cohort assessed the influence of participant body mass index on the E2–CPTP relationship. In women, a statistically significant inverse relationship between peritraumatic E2 and CPTP was observed (β = −0.280, P = 0.043) such that higher E2 levels predicted lower CPTP severity over time. Secondary analyses identified an E2 * body mass index interaction in men from the motor vehicle collision cohort such that obese men with higher E2 levels were at greater risk of developing CPTP. In nonobese men from the motor vehicle collision cohort and in men from the major thermal burn injury cohort, no statistically significant relationship was identified. In conclusion, peritraumatic circulating E2 levels predict CPTP vulnerability in women trauma survivors. In addition, these data suggest that peritraumatic administration of E2 might improve CPTP outcomes for women; further research is needed to test this possibility. Abstract : Supplemental Digital Content is Available in the Text.Assessment of longitudinal cohort data from male and female trauma survivors identified 17β-estradiol as a risk predictor and potential mediator of chronic pain development